2008
DOI: 10.5194/hess-12-751-2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil moisture fields estimated by catchment modelling and remote sensing: a case study in South Africa

Abstract: Abstract. The paper compares two independent approaches to estimate soil moisture at the regional scale over a 4625 km 2 catchment (Liebenbergsvlei, South Africa). The first estimate is derived from a physically-based hydrological model (TOPKAPI). The second estimate is derived from the scatterometer on board the European Remote Sensing satellite (ERS). Results show a good correspondence between the modelled and remotely sensed soil moisture, particularly with respect to the soil moisture dynamic, illustrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…For example, Kite and Droogers (2000) compared several hydrological models and satellite-based ET estimation methods, as well as field measurements. Spatial soil moisture fields derived from hydrological models have been compared to estimates derived from passive microwave observations (Liu et al, 2010) and radar (Vischel et al, 2008;Parajka et al, 2009). Biftu and Gan (2001) used AVHRR and Landsat LST and radar soil moisture to evaluate model results.…”
Section: Model Evaluation and Improvementmentioning
confidence: 99%
“…For example, Kite and Droogers (2000) compared several hydrological models and satellite-based ET estimation methods, as well as field measurements. Spatial soil moisture fields derived from hydrological models have been compared to estimates derived from passive microwave observations (Liu et al, 2010) and radar (Vischel et al, 2008;Parajka et al, 2009). Biftu and Gan (2001) used AVHRR and Landsat LST and radar soil moisture to evaluate model results.…”
Section: Model Evaluation and Improvementmentioning
confidence: 99%
“…A number of previous studies (Vischel et al, 2008;Brocca et al, 2010;Albergel et al, 2009;Gruhier et al, 2010;Rüdiger et al, 2009;Draper et al, 2009;Wagner et al, 2007) evaluated these passive and active microwave soil moisture products against in situ measurements and found that VUA-NASA passive microwave product performs better over sparsely vegetated regions, whereas the TU-Wien active microwave product shows better agreement for regions of moderate vegetation density. Over the sparsely to moderately vegetated regions, both products have similar performances.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly apparent when comparing models developed to represent the same process at different scales and for which different qualities of input variables, parameterization/initialization, and data for evaluation will be available, for example, soil water balances at plot, farm, catchment, and region (e.g., Keating et al 2002;Vischel et al 2007). This has led to the development of application-specific testing of models and the idea of model benchmarking, by comparing simulation outputs from different models, where outputs from one simulation can also be accepted as a "standard" (based on previous evaluations, e.g., Vanclay 1994).…”
Section: Dependence On the Contextmentioning
confidence: 99%